Hazard analysis and critical control point tool for the food industry - Khairunisa Amirah, Jamaludin (2025)
Ensuring food safety is critical for the food industry, where compliance with Hazard Analysis and Critical Control Point (HACCP) standards is vital for public health and business sustainability. Small and medium-sized enterprises (SMEs), which play a significant role in the food supply chain, face substantial challenges in implementing HACCP. These challenges stem from financial constraints, limited resources, and a reliance on manual processes that are prone to inefficiencies and human error. While digitalization offers transformative potential for food safety management, barriers such as high costs, technical complexity, and resistance to change hinder its adoption among SMEs. This study aimed to address these issues by developing a digital HACCP aid-tool tailored for SMEs in Malaysia. The study involved constructing a HACCP framework that focused on the first, second, third, and seventh principles of HACCP. The tool incorporates features such as a risk matrix for hazard analysis, decision trees for critical control points, and automated record-keeping using Microsoft Access. Although the Content Validity Index (CVI) score (0.83) did not meet the acceptable threshold (1.00), significant improvements were made to the tool based on expert opinions, enhancing its content reliability. A case study involving a local SME specializing in beef patties demonstrated the tool's applicability, while expert feedback was used to validate its content and functionality. Usability testing yielded a high System Usability Scale (SUS) score of 85, indicating the tool's effectiveness and user-friendliness. By addressing the limitations of manual HACCP management and providing a cost-effective digital solution, this study contributes to the digitalization of food safety management systems (FSMS) for SMEs. The findings highlight the potential of the developed tool to enhance compliance, operational efficiency, and food safety practices, paving the way for broader adoption of digital FSMS in the food industry.